The Influence of Government External Debt on Indonesia’s Economic Growth - Hidayat, Romi (Contemporary Society and Politics Journal, 2025)
This study aims to analyze the impact of government external debt on Indonesia’s economic growth. The research is grounded in the phenomenon of increasing dependence among developing countries, including Indonesia, on external financing sources as a means to support national development funding. However, the relationship between external debt and economic growth remains a subject of academic debate, as empirical findings on this issue tend to be contradictory. The study employs a quantitative approach using time series data. The data utilized are secondary in nature, obtained from official reports on Indonesia’s external debt. Data analysis was conducted using SPSS version 24, applying classical assumption tests and multiple linear regression analysis. The results indicate that the external debt variable has a significant effect on Indonesia’s economic growth. This is evidenced by a regression coefficient of 13.280 and a significance level of 0.000, which is below the standard significance threshold of α = 0.05. Accordingly, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. This suggests that government external debt makes a substantial contribution to the dynamics of national economic growth. The study affirms that in the Indonesian context, external debt can function as a supportive instrument for economic development, provided it is managed prudently and allocated toward productive sectors that have a direct impact on long-term economic growth.